2016
DOI: 10.1111/flan.12225
|View full text |Cite
|
Sign up to set email alerts
|

Chinese L2 Learners’ Depth of Vocabulary Knowledge and Its Role in Reading Comprehension

Abstract: Using a Chinese Word Associates Test (WAT‐C), this study examined the vocabulary depth of second language learners of Chinese and its contribution to the learners’ reading comprehension. Results showed no significant effects of word frequency, word class (i.e., adjectives vs. verbs), and type of association relationships (i.e., paradigmatic vs. syntagmatic) on learners’ WAT‐C performance. More important, vocabulary depth was found to be a significant and unique predictor of reading comprehension over and above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 44 publications
(108 reference statements)
6
26
0
4
Order By: Relevance
“…Both aspects of the depth of vocabulary knowledge, measured by paradigmatic relation and syntagmatic relation, and analytical relations jointly and significantly contributed to the dependent variable, academic reading comprehension. The result of the present study corroborated other previous findings of L2 learners of English (e.g., Qian 1998Qian , 1999Qian , 2002Li and Kirby 2015;Zhang and Yang 2016) even though the cited studies did not include morphological knowledge and analytical relations under the depth of vocabulary knowledge test. On the other hand, analytical relations of the depth of vocabulary knowledge contributed the most to explain the variance in academic reading comprehension than other parts of depth of vocabulary knowledge represented by both syntagmatic and paradigmatic relations and morphological knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both aspects of the depth of vocabulary knowledge, measured by paradigmatic relation and syntagmatic relation, and analytical relations jointly and significantly contributed to the dependent variable, academic reading comprehension. The result of the present study corroborated other previous findings of L2 learners of English (e.g., Qian 1998Qian , 1999Qian , 2002Li and Kirby 2015;Zhang and Yang 2016) even though the cited studies did not include morphological knowledge and analytical relations under the depth of vocabulary knowledge test. On the other hand, analytical relations of the depth of vocabulary knowledge contributed the most to explain the variance in academic reading comprehension than other parts of depth of vocabulary knowledge represented by both syntagmatic and paradigmatic relations and morphological knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, measures that have the capability of evaluating vocabulary depth knowledge efficaciously are crucially pursued. The rationale behind this is that so far L2/FL research have presented "a clear imbalance" (p. 699) concerning its multidimensionality, especially with respect to vocabulary depth knowledge (Zhang and Yang 2016).…”
Section: Knowledge Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that the VLT might have overlapped with the words found in the WAT and prevented the depth factor from attaining significance. On the contrary, Zhang & Yang (2016) revealed that lexical breadth and depth contributed differently across different L2 reading tasks. The researchers found that lexical depth contributed more to short texts while the contribution of lexical breadth was more to long reading tasks.…”
Section: Discussionmentioning
confidence: 87%
“…4) Another study should explore not only the vocabulary knowledge, here referring mostly to vocabulary size, but also the depth of vocabulary. Studies such as those of Qian (1999) and Zhang & Yang (2016), found that the depth of vocabulary knowledge was more indicator of reading comprehension. However, Li & Kirby (2014) did not find a statistically significant difference between size, i.e.…”
Section: Discussionmentioning
confidence: 98%